Figural language in the novel : the flowers of speech from Cervantes to Joyce - Saldívar, Ramón, 1949- (Princeton, New Jersey : Princeton University Press, 1984)
Novels affirm the power of fiction to portray the horizons of knowledge and to dramatize the ways that the truths of human existence are created and preserved. Professor Saldivar shows that deconstructive readings of novels remind us that we do not apprehend the world directly but through interpretive codes. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original te.
Cover; Table of Contents.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Fiction -- Technique; Fiction -- History and criticism; Narration (Rhetoric) -- History; Figures of speech; Roman -- Histoire et critique; Narration -- Histoire; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; Fiction; Fiction -- Technique; Figures of speech; Narration (Rhetoric); Criticism, interpretation, etc; History